BENTUK DAN GAYA BAHASA PANTUN PADA LIRIK LAGU CILOKAQ SASAK PEPAO-JANEPRIE DALAM ALBUM “SAQTEKANGEN” SERTA KAITANNYA DENGAN PEMBELAJARAN SASTRA - MUHAMMAD RIANDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
There are two problems in this research. First, what is the form and style of the rhyme language in the lyrics of the song Cilokaq Sasak Pepao-Janeprie in the album “Saqtekangen”; second, how it relates to literary learning. The purpose of this study is to describe the form and style of the rhyme language in the lyrics of the song Cilokaq Sasak Pepao-Janeprie in the album